Intellectual capital change management in the construction industry: The case of an inter-organisational collaboration - José Vale; Nádia Barbosa; Rui Bertuzi; Ana Maria Bandeira; Vera Teixeira Vale (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Nowadays, due to the complexity of the relationships with external entities, along with the importance that traditional media and the innovative social media have in creating competitive advantages, it is necessary for companies to collaborate in order to create Intellectual Capital (IC). Although collaboration is crucial to create IC, there is a paucity in literature regarding the effects that a specific type of collaboration may have on the IC of an organisation, specifically a franchising with a mediatic actor. Moreover, literature addressing IC creation and destruction over time is scarce, especially when applied to the construction industry. This paper's goal is twofold: understanding the longitudinal changes of a construction SME's Intellectual Capital, regarding its creation and destruction; analysing the impact that a specific inter-organisational collaboration franchising-with a mediatic actor may have on such IC. A single in-depth case study was conducted, allowing to conclude that the actions of an organisation can develop both Intellectual Assets and Intellectual Liabilities. It was also concluded that inter-organisational collaboration, through a franchise with an actor with experience in communication, can generate, in the long term, positive and innovative effects regarding the different IC components, namely the Relational one. More specifically, the paper allowed to ascertain that an organisation's IC changes over time in a dynamic fashion, i.e., Intellectual Liabilities which emerged before an innovative collaboration can be transformed into Intellectual Assets and create competitive advantages. This paper contributes to stress the importance of managing IC, not only when it is created, but namely in when it can be destroyed, in a context of inter-organisational collaborations applied to a construction SME.
Keywords: 650; collaboration; franchising; Intellectual Assets; Intellectual Capital; Intellectual Liabilities